Optimizing laboratory cultivation of wood-inhabiting fungi with emphasis on applied conservation - Crosier, Joette; von Longo-Liebenstein, Lorin; Edman, Mattias; Adamczyk, Sylwia; Hamberg, Leena (Springer Nature, 2025)
While fungi have been grown for centuries as food, cultivation knowledge rarely extends to rare fungi, usually confined to those with high biotechnology or food value. A more robust knowledge base on cultivating rare, challenging fungi may be critical for conservation, as many species face extinction. They should be cultivated for gene banks, reintroduction, and other conservation work. This study adapted mushroom growing techniques for seven threatened wood-inhabiting fungi, all red-listed in Finland and Sweden: Antrodia crassa, Antrodia infirma, Amylocystis lapponica, Skeletocutis stellae, Perenniporia tenuis, Radulodon erikssonii, and Haploporus odorus. We grew mycelium of these species (five strains each, two for P. tenuis) under various laboratory conditions. We tested wood dust supplementation (in agar), grain spawn substrate composition, gas exchange rates, two wood types (natural host and birch) on sawdust and dowel spawn, and temperature range (6.0–36.5 °C). We measured growth rate in all conditions and ergosterol (mycelial biomass indicator) in wood type and wood dust agar tests. We found wood dust–supplemented agar had an overall positive effect. Temperature effects varied by species, with some preferring relatively warm or cool temperatures, and some having a narrower growth range. Most species grew better on grain when vermiculite was added; gas exchange had no effect. Wood type had a variable effect, but birch was suitable in all cases, sometimes better than the natural host wood. Overall, our treatments had positive to neutral effects on mycelial growth of our fungal species.
Keywords: sawdust spawn; supplementation; temperature; substrate specificity; culture collections; grain spawn